2018
DOI: 10.1080/2162402x.2018.1534038
|View full text |Cite
|
Sign up to set email alerts
|

ISG20 promotes local tumor immunity and contributes to poor survival in human glioma

Abstract: Recent evidence has confirmed that a mutation of the isocitrate dehydrogenase (IDH) gene occurs early in gliomagenesis and contributes to suppressed immunity. The present study aimed to determine the candidate genes associated with IDH mutation status that could serve as biomarkers of immune suppression for improved prognosis prediction. Clinical information and RNA-seq gene expression data were collected for 932 glioma samples from the CGGA and TCGA databases, and differentially expressed genes in both lower-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“…In human glioma, ISG20 was positively correlated to immune checkpoints (PD-1 and PD-L1) and suppressed the adaptive immune response. In addition, high expression of ISG20 predicted poor overall survival in glioma [52]. Similarly, patients with high expression of ISG20 had shorter overall survival time in our present study.…”
Section: Discussionsupporting
confidence: 81%
“…In human glioma, ISG20 was positively correlated to immune checkpoints (PD-1 and PD-L1) and suppressed the adaptive immune response. In addition, high expression of ISG20 predicted poor overall survival in glioma [52]. Similarly, patients with high expression of ISG20 had shorter overall survival time in our present study.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, we screened out genes significant to survival of melanoma patients, majority of them were verified to associated with tumors. ISG20 has interferon-related antiviral effects, while a study found that over-expression of ISG20 promotes metastasis and angiogenesis of liver cancer cells (Gao et al, 2019). DTL is involved with the regulation of cell cycles and playing a role in the regulation of DNA damage, so we suggest hat it regulate cycle of melanocytes so that to regulate its progression.…”
Section: Discussionmentioning
confidence: 85%
“…The ISG20 gene was first introduced by Gongora et al (1997) as a promyelocytic leukemia nuclear body (PML-NB)-associated protein. The expression of ISG20 is reduced in IDH mutant tumors and ISG20 can promote local tumor immunity and may serve as a potential therapeutic target of human glioma (Gao et al, 2019). This is very interesting: all these identified genes are somehow related to interferons and/or immune response.…”
Section: Discussionmentioning
confidence: 99%